«NO CHILD'S LITERATURE: ARTISTIC PICTURE OF WORLD IN ROMANI OF MARINA AND SERGEY DYACHENCO «WILD ENERGY. LANA» - Чобанюк, В. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the fantastic novel of Marina and Sergey Dyachenco is explored "Wild energy. Lana", turned to the young generation above all things.